A Ho3+‐Based Luminescent Thermometer for Sensitive Sensing over a Wide Temperature Range. Issue 1 (8th November 2020) - van Swieten, Thomas P.; Yu, Dechao; Yu, Ting; Vonk, Sander J. W.; Suta, Markus; Zhang, Qinyuan; Meijerink, Andries; Rabouw, Freddy T.
Abstract: Luminescence thermometry is used in a variety of research fields for noninvasive temperature sensing. Lanthanide‐doped micro‐/nanocrystals are exceptionally suitable for this. The popular concept of luminescence‐intensity‐ratio thermometry is based on emission from thermally coupled levels in a single lanthanide ion, following Boltzmann's law. These thermometers can measure temperature with low uncertainty, but only in a limited temperature range. In this work, a Ho 3+ ‐based thermometer is presented and quantitatively modeled with sustained low temperature uncertainty from room temperature up to 873 K. The thermometer shows bright green and red luminescence with a strong and opposite dependence on temperature and Ho 3+ concentration. This is the result of temperature‐dependent competition between multi‐phonon relaxation and energy transfer, feeding the green‐ and red‐emitting levels, respectively, following excitation with blue light. This simple and quantitative model of this competition predicts the output spectrum over a wide range of temperatures (300–873 K) and Ho 3+ concentrations (0.1–30%). The optimum Ho 3+ concentration can thus be determined for reliable measurements over any temperature range of interest. Quantitative modeling as presented here is crucial to optimally benefit from the potential of energy‐transfer thermometers to achieve low measurement uncertainties over a wide temperature range. Abstract : The emission of Ho 3+ ‐doped crystals can be used for remote thermometry. This work builds a quantitative model of how the emission color depends on temperature and Ho 3+ doping concentration. The model demonstrates how tuning the Ho 3+ doping concentration results in the most reliable temperature measurements.